Black Catholic Conversion and the Burden of Black Religion - Cressler, Matthew J. (Journal of Africana religions, 2014)
This article is a contribution to the roundtable discussion of Black Catholicism. African American converts to Catholicism in the United States have often been viewed with skepticism because of the preconceived notion that African Americans are naturally evangelical and Protestant. As a result, scholars have resorted to functionalist explanations of Black Catholic conversion, presuming African Americans convert for social or economic advantages. Letters written by Black Catholic converts themselves, however, challenge these narrow functionalist explanations and illuminate the complex pressures and motivations that often led to conversion. Attention to Black Catholic converts can thus help us unburden the study of “Black religion” by calling attention to alternative modes of African American religious life and practice.